1984
DOI: 10.1002/macp.1984.021850901
|View full text |Cite
|
Sign up to set email alerts
|

Study of the state of titanium ions and the composition of the active component in titanium‐magnesium catalysts for ethylene polymerization

Abstract: The state of Ti3+ ions formed at various steps of preparation and activation of highly active titanium-magnesium catalysts of various composition (dry milling of TiC13 with MgCl,; reduction of T i c 4 by nonsolvated magnesium dialkyl; interaction of the TiC14/MgCl s stem with an organoaluminium compound) was studied by the ESR method. It was found that In all systems studied the same three types of Ti3+ ions in the chlorine environment are formed, differing in coordination and localization sites in MgCI,. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 21 publications
6
67
0
Order By: Relevance
“…[16] In TiCl 4 -based ZN catalysts, a series of ESR studies proved that Ti species formed aggregates in the course of reduction with alkylaluminum. [13][14][15] Our recent computational study showed that reduced Ti species can aggregate with each other also on the MgCl 2 (110) surface to form isospecific and ESR-silent active sites, [10] although it had been conventionally believed that Ti species could form multi-nuclear species only on the (100) surface to be the sole isospecific origin. [8] That is, the broad peak at ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] In TiCl 4 -based ZN catalysts, a series of ESR studies proved that Ti species formed aggregates in the course of reduction with alkylaluminum. [13][14][15] Our recent computational study showed that reduced Ti species can aggregate with each other also on the MgCl 2 (110) surface to form isospecific and ESR-silent active sites, [10] although it had been conventionally believed that Ti species could form multi-nuclear species only on the (100) surface to be the sole isospecific origin. [8] That is, the broad peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…The stereoregularity (mmmm) was determined by 13 C NMR (Varian Gemini-300 spectrometer) at 120 8C using hexachloro-1,3-butadiene as a diluent and 1,1,2,2-tetrachloroethane-d 2 was added as an internal lock and reference. Temperature-rising elution fractionation (TREF) was performed with an online system (Senshu SSC-7300) using ODCB.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicate that the is the effective Al/Ti ratio present, the reactions are believed to be quite complicated. 4,38 Although it appears that besides present initially in the system. Because of the acting as a reducing agent, TEA also participates complex side reactions involved in supported catain the active site formation through the formation lysts, the experimental Al/Ti ratio is often much of bimetallic active centers, 18,39 the true nature of greater than the stoichiometric ratio.…”
Section: Effect Of Catalyst Agingmentioning
confidence: 97%
“…[1][2][3] In spite of ical measurements. Using techniques such as electron spin resonance spectrometry (ESR), 4 their successful applications in industrial practice, a complete knowledge of these catalyst systems is photometry, 5 chemical ionization-mass spectrometry (CI-MS), 6 X-ray absorption spectrosstill lacking. Some of the unresolved issues relate to the active site structure and its formation, as well copy, 7 and chemical titration methods, 5,8 the occurrence of oxidation state reduction upon the as the role of components such as the cocatalyst and electron donor and their influence on the catalyst mixing of catalyst and cocatalyst has been confirmed.…”
Section: Introductionmentioning
confidence: 99%